The Edukasi Konsep Kewirausahaan Sosial Berbasis Potensi Desa Melalui Badan Umum Milik Desa (BUMDES) - Wella Sandria; Arniwita Arniwita; Siswoyo Siswoyo; Hario Tamtomo; Hetty Rohayani; Ermaini Ermaini (Journal of Social Responsibility Projects by Higher Education Forum, 2026)
Village potential-based social entrepreneurship through Village-Owned Enterprises (BUMDes) represents a social business model that optimizes natural resources, cultural assets, and community capacities to address socio-economic issues while increasing Village Original Revenue (PADes). This community service activity was conducted in Muara Tembesi Subdistrict, Batanghari Regency, Jambi, Indonesia. The study aims to analyze the role of Village-Owned Enterprises (BUMDes) in village development and improving community welfare through a social entrepreneurship approach. There are 15 actively operating BUMDes distributed across 12 villages in Muara Tembesi, engaging in various types of business activities. Although these enterprises have achieved progress in managing their business units, they still face several challenges related to social entrepreneurship, including a lack of innovation in the creative economy for resource management, inadequate mapping of village potential, suboptimal utilization of village websites, and limited effectiveness in marketing and promotional channels. Based on these issues, the service team conducted field observations and provided technical assistance to BUMDes managers, carried out village potential mapping, and analyzed appropriate strategies for developing business units and creative economic activities within rural communities. The results of the mapping indicate that each village possesses distinct potentials; however, natural resource outputs are still predominantly concentrated in the agricultural and plantation sectors. Several strategies were proposed to address the challenges faced by BUMDes, including enhancing understanding of the importance of BUMDes for village development, providing training and mentoring in social entrepreneurship and small and medium enterprise management, increasing community awareness of village potential, and encouraging subdistrict and village officials to utilize BUMDes operational funds more effectively.